Male/infant interactions in the chimpanzee. - Davis, Diana L. (My University, 1980)
Adult male/infant interactions were observed in captive chimpanzees, housed at the Chimpanzee Sign Language Laboratory in Norman, Oklahoma. The focal points of the study were maternal restrictiveness and its relationship to the quality and quantity of adult male/infant interactions. Video tape analysis was utilized and data were recorded over a four month period. In the initial episodes, maternal restrictiveness was found to be an important variable in the degree to which the male and infant interacted. This restrictiveness decreased with time and an intense social bond between the male and infant was formed.
Keywords: Psychology, Developmental.